Sundathelphusa tuerkayi, a new species of gecarcinucid freshwater crab (Crustacea: Brachyura) from Lombok Island, Indonesia - Ng,Peter K. L. (2016)
Abstract A new species of the freshwater crab genus Sundathelphusa Bott, 1969 is described from the Indonesian island of Lombok. Sundathelphusa tuerkayi, new species, appears to be most closely related to Sundathelphusa aruana (Roux, 1911), which is known for certain only from the Aru Islands, but differs from it and all other congeners by a unique combination of morphological characters. The new crab hosts a small ectosymbiotic temnocephalid flatworm, possibly belonging to the genus Temnosewellia Damborenea and Cannon, 2001 (Platyhelminthes: Temnocephalida).